Stigma Sensitivity and the Duration of Temporary Closure Are Affected by Pollinator Identity in Mazus miquelii (Phrymaceae), a Species with Bilobed Stigma - Jin, Xiao-Fang; Ye, Zhong-Ming; Amboka, Grace M.; Wang, Qing-Feng; Yang, Chun-Feng (Frontiers in Plant Science, 2017)
A sensitive bilobed stigma is thought to assure reproduction, avoid selfing and promote outcrossing. In addition, it may also play a role in pollinator selection since only pollinators with the appropriate body size can trigger this mechanism. However, no experimental study has investigated how the sensitive stigma responds to different pollinators and its potential effects on pollination. Mazus miquelii (Phrymaceae), a plant with a bilobed stigma was studied to investigate the relationship between stigma behaviors and its multiple insect pollinators. The reaction time of stigma closure after touched, duration of temporary closure, and factors determining permanent closure of the stigma were studied when flowers were exposed to different visitors and conducted with hand pollination. Manual stimulation was also used to detect the potential differences in stigmas when touched with different degrees of external forces. Results indicated that, compared to pollinators with a small body size, larger pollinators transferred more pollen grains to the stigma, causing a rapid stigma response and resulting in a higher percentage of permanent closures. Duration of temporary closure was negatively correlated with the speed of stigma closure; a stigma that closed more rapidly reopened more slowly. Manual stimulation showed that reaction time of stigma closure was likely a response to external mechanical forces. Hand pollination treatments revealed that the permanent closure of a stigma was determined by the size of stigmatic pollen load. For large pollinators, the speedy reaction of the stigma might help to reduce pollen loss, enhance pollen germination and avoid obstructing pollen export. Stigmas showed low sensitivity when touched by inferior pollinators, which may have increased the possibility of pollen deposition by subsequent visits. Therefore, the stigma behavior in M. miquelii is likely a mechanism of pollinator selection to maximize pollination success.